Analisis Yuridis Perbuatan Sala Pela Menurut Perkawinan Adat Nagekeo Di Desa Wolokisa, Kecamatan Mauponggo, Kabupaten Nagekeo - Maria Adriana Mogi; Juliana Susantje Ndolu; Petornius Damat (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Sala Pela is considered a serious violation of customary marriage law within the Nagekeo indigenous community because it infringes moral values, kinship principles, and social harmony. This study aims to identify the forms of conduct categorized as Sala Pela and to analyze the customary legal mechanisms for resolving such violations in Wolokisa Village, Mauponggo District, Nagekeo Regency. This research employed an empirical legal research method using a qualitative approach. Data were collected through interviews with customary leaders, village officials, and community members, supported by library research on relevant legislation and legal literature. The findings reveal that Sala Pela includes incestuous relationships, prohibited marriages between close relatives, and illicit relationships involving in-laws. The settlement process is carried out through reporting to customary leaders, customary deliberation, the imposition of customary sanctions, and traditional rituals aimed at restoring social and spiritual balance. However, the implementation of customary sanctions is constrained by economic limitations, evidentiary issues, and social stigma. Therefore, strengthening customary legal education and providing greater protection for affected parties are necessary to ensure that customary law continues to uphold restorative justice.